2021
DOI: 10.1515/znc-2021-0042
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antioxidant, antimicrobial and antiviral docking studies of ethyl 2-(2-(arylidene)hydrazinyl)thiazole-4-carboxylates

Abstract: A series of ethyl 2-(2-(arylidene)hydrazinyl)thiazole-4-carboxylates (2a–r) was synthesized in two steps from thiosemicarbazones (1a–r), which were cyclized with ethyl bromopyruvate to ethyl 2-(2-(arylidene)hydrazinyl)thiazole-4-carboxylates (2a–r). The structures of compounds (2a–r) were established by FT-IR, 1H- and 13C-NMR. The structure of compound 2a was confirmed by HRMS. The compounds (2a–r) were then evaluated for their antimicrobial and antioxidant assays. The antioxidant studies revealed, ethyl 2-(2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The up‐field carbon signals in range δ 55.3–56.2 ppm were assigned to the methoxy carbons. The synthesis of compounds was further confirmed when NMR spectra were compared with literature reported similar skeleton compounds [38–45] …”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The up‐field carbon signals in range δ 55.3–56.2 ppm were assigned to the methoxy carbons. The synthesis of compounds was further confirmed when NMR spectra were compared with literature reported similar skeleton compounds [38–45] …”
Section: Resultsmentioning
confidence: 71%
“…The synthesis of compounds was further confirmed when NMR spectra were compared with literature reported similar skeleton compounds. [38][39][40][41][42][43][44][45] After establishing the synthesis of the expected hydrazinyl-4-methoxyphenylthiazoles their biological significance was investigated by α-amylase inhibitory potential, antiglycation activity, antioxidant potential and cytotoxic behaviour by haemolytic assay.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that some thiosemicarbazone compounds have antiviral effects on the SARS-CoV-2 as bioinformatically. [31][32][33] The effects of complex 2 on cell viability in BEAS-2B cells were measured by MTT cell viability test. As a result of the experiments, it was found that 2 had a proliferative effect at low doses.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that some thiosemicarbazone compounds have antiviral effects on the SARS‐CoV‐2 as bioinformatically. [ 31–33 ]…”
Section: Resultsmentioning
confidence: 99%
“…Various oxygen-containing azoles, as exemplified by oxadiazoles, oxazoles, and isoxazoles, have been also thoroughly studied for their diversified biological activities. Widely used as potent antifungal agents (fungicides) due to their valuable properties like broad spectrum of action, chemical stability, and oral bioavailability [39][40][41][42], various azole derivatives have also demonstrated many other promising biological properties including antidiabetic, immunosuppressant, antiinflammatory, antiviral, antitubercular, and anticancer activities [8,12,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%